Bifunctional Anti-Human Immunodeficiency Virus Type 1 Small Molecules with Two Novel Mechanisms of Action - Huang, Li (American Society for Microbiology, 2004)
A class of betulinic acid derivatives was synthesized to target two critical steps in the human immunodeficiency virus type 1 (HIV-1) replication cycle, entry and maturation. Each mechanism of HIV-1 inhibition is distinct from clinically available anti-HIV therapeutics. The viral determinants of the antientry and antimaturation activities are the bridging sheet of HIV-1 gp120 and the P24/p2 cleavage site, respectively.